LOS NUEVOS SISTEMAS INTELIGENTES DE TRANSPORTE PARA UNA CIUDAD EN DESARROLLO, LIMA PERÚ - Martínez, Manuel J (2019)
This paper presents eight services of Intelligent Transportation Systems modified to fit a developing city in a motorization process, to improve transit attractiveness over auto and taxi, and thus reducing congestion and pollution.